2006
DOI: 10.1038/nbt1251
|View full text |Cite
|
Sign up to set email alerts
|

Redirection of cytosolic or plastidic isoprenoid precursors elevates terpene production in plants

Abstract: Terpenes constitute a distinct class of natural products that attract insects, defend against phytopathogenic microbes and combat human diseases. However, like most natural products, they are usually made by plants and microbes in small amounts and as complex mixtures. Chemical synthesis is often costly and inefficient, and may not yield enantiomerically pure terpenes, whereas large-scale microbial production requires expensive feedstocks. We engineered high-level terpene production in tobacco plants by divert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
341
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(349 citation statements)
references
References 29 publications
4
341
3
1
Order By: Relevance
“…The availability of GDP and FDP are often the key factor in the production of monoterpenes and sesquiterpenes in plants. This problem was elegantly overcome in metabolic engineering experiments by the co-expression of GDP and FDP synthases with appropriate monoterpene and sesquiterpene synthases over-expressed in tobacco (Wu et al, 2006). This strategy, together with targeting of the overexpression to the plastid compartment, resulted in increased synthesis of the sesquiterpenes amorpha-4,11-diene and patchoulol and the monoterpene S-limonene (Wu et al, 2006).…”
Section: Carbohydrate-derived Flavor Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of GDP and FDP are often the key factor in the production of monoterpenes and sesquiterpenes in plants. This problem was elegantly overcome in metabolic engineering experiments by the co-expression of GDP and FDP synthases with appropriate monoterpene and sesquiterpene synthases over-expressed in tobacco (Wu et al, 2006). This strategy, together with targeting of the overexpression to the plastid compartment, resulted in increased synthesis of the sesquiterpenes amorpha-4,11-diene and patchoulol and the monoterpene S-limonene (Wu et al, 2006).…”
Section: Carbohydrate-derived Flavor Compoundsmentioning
confidence: 99%
“…In addition, this tool is being used more and more for the understanding of chemical diversity in crops (K枚 llner et al, 2004;Portnoy et al, 2008), as well as improvement of traits in crops such as disease and pest resistance (Kappers et al, 2005;Schnee et al, 2006;Wu et al, 2006), enhanced and altered aroma formation (Lavy et al, 2002;Lewinsohn et al, 2001;Mahmoud and Croteau, 2001) and production of medicinal compounds (Wu et al, 2006). Most of the recent progress in this field has been summarized by L眉 cker et al (2007).…”
Section: Carbohydrate-derived Flavor Compoundsmentioning
confidence: 99%
“…By introduction of potent antimalarial drug (artemisinin) in tobacco via two mega biosynthetic pathways into the nuclear genomes and chloroplasts, resulted in enhanced level of artemisinin without interrupting plant health. A comprehensive evaluation was conducted by Wu et al (2006) to evaluate the effect of targeting different gene products to cytosol or plastids. The most appropriate example is the accumulation of amorpha-4,11-diene (ADS) and FPS in plastids, resulting in approximately a 5000-fold increase in ADS concentration in model tobacco plants over another model plant (unchanged ADS gene) having a cytosolic gene product (Wu et al 2006).…”
Section: Subcellular Localizationmentioning
confidence: 99%
“…A comprehensive evaluation was conducted by Wu et al (2006) to evaluate the effect of targeting different gene products to cytosol or plastids. The most appropriate example is the accumulation of amorpha-4,11-diene (ADS) and FPS in plastids, resulting in approximately a 5000-fold increase in ADS concentration in model tobacco plants over another model plant (unchanged ADS gene) having a cytosolic gene product (Wu et al 2006). Likewise, a mitochondrial-localized heterologous TPS gene was first studied by Kappers et al (2005), which revealed that the overexpression of the FaNES1 gene from strawberry in the model Arabidopsis plant with an engineered 'Met' mitochondrial targeting sequence resulted in two new terpenoids involved in attracting predatory mites that potentially aid in defense against herbivores.…”
Section: Subcellular Localizationmentioning
confidence: 99%
“…In a pioneering experiment, N. tabacum was transformed by amorphadiene synthase gene (ADS) cloned from A. annua, leading to the accumulation of amorpha-1,4-diene, a committed precursor of artemisinin, in trace amounts (Wallaart et al 2001). After years, an innovative strategy has been used to increase the substantial accumulation of amorpha-1,4-diene in N. tabacum, in which ADS gene from A. annua and farnesyl pyrophosphate synthase gene (FPS) from chicken were designed to be expressed in nucleus and targeted to plastid, resulting in 5,000-fold increases of amorpha-4,11-diene (Wu et al 2006). Later, three newly cloned artemisinin biosynthesis genes including cytochrome P450 monooxygenase gene (CYP71AV1), artemisinic aldehyde D11(13) double bond reductase gene (DBR2), and aldehyde dehydrogenase 1 gene (ALDH1), were introduced into transgenic N. tabacum plant cells that express ADS and accumulate amorpha-4,11-diene.…”
Section: Introductionmentioning
confidence: 99%